Medium energy ion irradiation of Ge surface – search for a better understanding of the surface nano‐patterning. (2nd February 2016) - Kumar, Pravin; Jain, Priyanka; Sulania, Indra
Abstract : We report the morphological changes on Ge surfaces upon 50 keV Ar + and 100 keV Kr + beam irradiation at 60° angle of incidence. The Ge surfaces having three different amorphous–crystalline (a/c) interfaces achieved by the pre‐irradiation of 50 keV Ar + beam at 0°, 30° and 60° with a constant fluence of 5 × 10 16 ions/cm 2 were further processed by the same beam at higher fluences viz. 3 × 10 17, 5 × 10 17, 7 × 10 17 and 9 × 10 17 ions/cm 2 to understand the mechanism of nano‐scale surface patterning. The Kr + beam irradiation was carried out only on three fresh Ge surfaces with ion fluences of 3 × 10 17, 5 × 10 17 and 9 × 10 17 ions/cm 2 to compare the influence of projectile mass on surface patterning. Irrespective of the depth of a/c interface, the nanoscale surface patterning was completely missing on Ge surface with Ar + beam irradiation. However, the surface patterning was evidenced upon Kr + beam irradiation with similar ion fluences. The wavelength and the amplitude of the ripples were found to increase with increasing ion fluence. In the paper, the mass redistribution at a/c interface, the incompressible solid flow through amorphous layer, the angular distribution of sputtering/backscattering yields and the generation of non‐uniform stress across the amorphous layer are discussed, particularly in analogy with low energy experiments, to get better understanding of the mechanism of nanoscale surface patterning by the ion beams. Copyright © 2016 John Wiley & Sons, Ltd.